Determinación de los requerimientos hídricos del cultivo de zucchini (Cucurbita pepo L.), mediante el lisímetro volumétrico en la parroquia Malacatos sector San José. - Gallegos Tandazo, Edwin Benjamín (2019)
The present investigation was carried out in the San José neighbourhood belonging to parish of Malacatos, whose location is 30 Km from the city of Loja. The main objective of this research was to contribute to the efficient use of water in the San José sector which belongs to the Campana-Malacatos irrigation system. The study area was 35 m2, where two volumetric lysimeters of 1 m2 each were installed and within which the zucchini crop was sown at a planting density of 0.6 m between plants and 0.8 m between rows. For the evapotranspiration of the reference crop (ETo) a value of 4.63 mm/day was obtained, and the estimated crop evapotranspiration (ETc) was 3.69 mm/day. The values obtained from the crop coefficient (Kc) for zucchini were: in the germination phase 20 days Kc=0.72; vegetative growth phase 40 days Kc=0.90, thus obtaining an average of Kc 0.80 during the 120 days that the crop cycle lasted. The total water requirement for the entire zucchini crop cycle was 464.70 litres/m2, equivalent to 4647 m3/ha with a yield of 22.96 Kg/m2, equivalent to 229.6 Tn/ha. Having calculated the water consumption/performance ratio, it was determined that 20.24 litres of water were needed to produce 1 Kg of zucchini. Keywords: Volumetric lysimeter, Evapotranspiration, Crop coefficient, Yield.